PROSES LEGISLASI PERUBAHAN UNDANG-UNDANG PERKOPERASIAN - Ahmad Juwaini; Kristiany Parura; Dyah Ayu Pitaloka (Universitas Muhammadiyah Jember, 2020)
Cooperative as a pillar of the Indonesian economy, its position is very important for the people of Indonesia. The law (Act) governing Koperasi is Law No. 25 of 1992 concerning Cooperative. Due to the development of Indonesian society and various problems around Cooperative, it is necessary to make changes to the Cooperative Law. This research is to find out what are the changes in the Cooperative Law and how the legislative process changes the Cooperative Law after the cancellation of Law No. 17 of 2012. The results of the study show that the contents of the changes in the Cooperative Law are the status of establishment and articles of association, membership, organizational instruments, Cooperative capital, business results, business activities, supervision, merger, dissolution, empowerment of Koperasi and sanction provisions. The legislative process of the Cooperative Law by the DPR for the period 2014 - 2019 has been postponed for ratification and will be continued by the DPR for the 2019-2024 Period.